A muscle-liver-fat signalling axis is essential for central control of adaptive adipose remodelling - Shimizu, Noriaki; Maruyama, Takako; Yoshikawa, Noritada; Matsumiya, Ryo; Ma, Yanxia; Ito, Naoki; Tasaka, Yuki; Kuribara-Souta, Akiko; Miyata, Keishi; Oike, Yuichi; Berger, Stefan; Schütz, Günther; et al. (Nature Communications, 2015)
Skeletal muscle has a pleiotropic role in organismal energy metabolism, for example, by storing protein as an energy source, or by excreting endocrine hormones. Muscle proteolysis is tightly controlled by the hypothalamus-pituitary-adrenal signalling axis via a glucocorticoid-driven transcriptional programme. Here we unravel the physiological significance of this catabolic process using skeletal muscle-specific glucocorticoid receptor (GR) knockout (GRmKO) mice. These mice have increased muscle mass but smaller adipose tissues. Metabolically, GRmKO mice show a drastic shift of energy utilization and storage in muscle, liver and adipose tissues. We demonstrate that the resulting depletion of plasma alanine serves as a cue to increase plasma levels of fibroblast growth factor 21 (FGF21) and activates liver-fat communication, leading to the activation of lipolytic genes in adipose tissues. We propose that this skeletal muscle-liver-fat signalling axis may serve as a target for the development of therapies against various metabolic diseases, including obesity.